2016
DOI: 10.1021/acscombsci.6b00058
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Reaction Conditions for Amide Bond Formation in DNA-Encoded Combinatorial Libraries

Abstract: DNA-encoded combinatorial libraries are increasingly being used as tools for the discovery of small organic binding molecules to proteins of biological or pharmaceutical interest. In the majority of cases, synthetic procedures for the formation of DNA-encoded combinatorial libraries incorporate at least one step of amide bond formation between amino modified DNA and a carboxylic acid. We investigated reaction conditions and established a methodology by using 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide, 1-hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
101
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(107 citation statements)
references
References 32 publications
1
101
0
2
Order By: Relevance
“…Although EDC/HOAt/DIPEA is often the system of choice, [14] we found that coupling with DMTMM-BF 4 /NMM was better in most cases,r esulting in higher conversions and cleaner products.E DC/HOAt/DIPEA was only superior for strained cyclic secondary amino acids and tyrosine derivatives,aproblem that likely stems from the reaction of the tyrosine hydroxy group with DMTMM-BF 4 /NMM. Although EDC/HOAt/DIPEA is often the system of choice, [14] we found that coupling with DMTMM-BF 4 /NMM was better in most cases,r esulting in higher conversions and cleaner products.E DC/HOAt/DIPEA was only superior for strained cyclic secondary amino acids and tyrosine derivatives,aproblem that likely stems from the reaction of the tyrosine hydroxy group with DMTMM-BF 4 /NMM.…”
mentioning
confidence: 75%
“…Although EDC/HOAt/DIPEA is often the system of choice, [14] we found that coupling with DMTMM-BF 4 /NMM was better in most cases,r esulting in higher conversions and cleaner products.E DC/HOAt/DIPEA was only superior for strained cyclic secondary amino acids and tyrosine derivatives,aproblem that likely stems from the reaction of the tyrosine hydroxy group with DMTMM-BF 4 /NMM. Although EDC/HOAt/DIPEA is often the system of choice, [14] we found that coupling with DMTMM-BF 4 /NMM was better in most cases,r esulting in higher conversions and cleaner products.E DC/HOAt/DIPEA was only superior for strained cyclic secondary amino acids and tyrosine derivatives,aproblem that likely stems from the reaction of the tyrosine hydroxy group with DMTMM-BF 4 /NMM.…”
mentioning
confidence: 75%
“…Several efficient strategies for the synthesis of DNA‐encoded peptides are used . Most protocols rely on Fmoc‐protected amino acids and the water‐soluble coupling reagent 4‐(4,6dimethoxy‐1,3,5‐triazin‐2‐yl)‐4‐methylmorpholinium chloride (DMT‐MM).…”
Section: Resultsmentioning
confidence: 99%
“…[12,22,23] The construction of large DNAencoded chemical libraries crucially relies on the availability of 'robust' reactions, which can be performed in water, are DNA-compatible, [24 -26] and which accept a large number of structurally diverse substrates. One of the most widely used reactions for the construction of DNA-encoded chemical libraries is the formation of amide bonds, since excellent procedures are available, [24,27] and since thousands of building blocks (e. g., amines and carboxylic acids) can be purchased from commercial sources at moderate costs. However, even a robust reaction such as amide bond formation with DMT-MM methodology displays acceptable conversion yields only for approximately 44 % of carboxylic acids.…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, improved methodologies are constantly being explored. [27] In this work, we aimed at implementing and optimizing copper and palladium-catalyzed reactions, which could be readily used for the construction of DNA-encoded chemical libraries. [28 -31] We focused on Suzuki cross-coupling, Sonogashira cross-coupling, and copper(I)-catalyzed alkyne-azide cycloaddition (CuAAC).…”
Section: Introductionmentioning
confidence: 99%